2012
DOI: 10.1666/10-153r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny, functional morphology, and comparative morphology of lower (Stage 4) and basal middle (Stage 5) Cambrian gogiids, Guizhou Province, China

Abstract: Three gogiid eocrinoids, numbering in the thousands of specimens, are well known from the lower Cambrian (Stage 4) Balang Formation (Guizhoueocrinus yui) and basal middle Cambrian (Stage 5) Kaili Formation (Kaili Biota) (Sinoeocrinus lui and Globoeocrinus globulus) that resided on the Yangtze-South China Plate (modern Guizhou Province, China). In each species a complete ontogenetic sequence, using thecal height (TH) as a scale, juvenile stage (early, middle, and late substages), mature stage (early, middle, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…This important study of Gogia sp., in which statistically analyzed a large amount of material, showed that post-metamorphic development most probably represents a continuous process. There are no statistical support for any of the size groupings separated previously by Parsley & Zhao (2006) and Parsley (2012) .We agree with the opinion that a separation of distinct ontogenetic stages based only on TH represents an artificial classification . On the basis of additional, newly analyzed material, we suspect that TH is insufficient to completely distinguish the three stages, although the limited number of specimens and partial knowledge of the complete population of the Jince material somewhat restricts our analyses.…”
Section: B Acontrasting
confidence: 52%
See 2 more Smart Citations
“…This important study of Gogia sp., in which statistically analyzed a large amount of material, showed that post-metamorphic development most probably represents a continuous process. There are no statistical support for any of the size groupings separated previously by Parsley & Zhao (2006) and Parsley (2012) .We agree with the opinion that a separation of distinct ontogenetic stages based only on TH represents an artificial classification . On the basis of additional, newly analyzed material, we suspect that TH is insufficient to completely distinguish the three stages, although the limited number of specimens and partial knowledge of the complete population of the Jince material somewhat restricts our analyses.…”
Section: B Acontrasting
confidence: 52%
“…In the first two papers, an informal classification of ontogenetic development of Gogia was proposed. Parsley (2012) distinguished several ontogenetic stages using thecal height (TH = the distance from the summit of the theca to the top of the stalk) as a scale, complemented by five identifying characters that are important for ontogeny. Based on three Chinese species, Guizhocrinus yui, Sinoeocrinus lui and Globoeocrinus globulus, a complete ontogenetic sequence was established with three different stages: (a) juvenile stage (with early, middle and late substages); (b) mature stage (early, middle and late substa- Figure 6.…”
Section: Ontogeny Of Eocrinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…eocrinoids, rhombiferans) (see e.g. Parsley 2009Parsley , 2012Zamora et al 2013a, this volume;Nohejlová & Fatka 2016).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…The stem is polyplated and clearly less organized than the aboral appendages of more derived edrioblastoids (e.g., Astrocystites). The holdfast is also polyplated, relatively wide, and very gogiid-like (see Sprinkle 1973;Parsley 2012). The holdfast of the holotype of C. guolensis is attached to a trilobite pygidium, suggesting that edrioblastoids were living as skeletal cementers on soft substrates in quiet environmental conditions.…”
Section: Attachment Strategies In Cambrian Edrioblastoidsmentioning
confidence: 99%